2001
DOI: 10.1046/j.1365-2133.2001.04521.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of hyperpigmentation in seborrhoeic keratosis involves the high expression of endothelin-converting enzyme-1alpha and TNF-alpha, which stimulate secretion of endothelin 1

Abstract: These findings suggest that the increased secretion of ET-1 leading to enhanced pigmentation in SK results from the co-ordinated increased expression of TNF-alpha and ECE-1alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 16 publications
3
51
0
2
Order By: Relevance
“…When SP binds to NK1R, SP-NK1R-b-arrestin forms a signalosome and is endocytosed with ECE1 on the cell surface, generating an early endosome in which ECE1 disrupts the SP-NK1R complex potentially by degrading SP and inducing NK1R recycling to the plasma membrane (Roosterman et al, 2007;Pelayo et al, 2011). In addition to the role of ECE1 as a regulator of the endocytic signaling of SP-NK1R, ECE1 is a known key enzyme that mediates melanogenesis by catalyzing the specific cleavage of inactive Big-EDN1 to produce an active EDN1 in keratinocytes and endothelial cells (Yanagisawa et al, 1988;Kido et al, 1997), as demonstrated by the increased level of secreted EDN1 in several hyperpigmented lesions (Manaka et al, 2001). ECE1 regulates the endocytic signaling and trafficking of SP1-NK1R and activates EDN1 via direct cleavage; therefore, we initially hypothesized that SP-NK1R-dependent endocytosed ECE1 interacts with and cleaves the inactive Big-EDN1 residing within vesicles in the secretory pathway in human melanocytes.…”
Section: Discussionmentioning
confidence: 96%
“…When SP binds to NK1R, SP-NK1R-b-arrestin forms a signalosome and is endocytosed with ECE1 on the cell surface, generating an early endosome in which ECE1 disrupts the SP-NK1R complex potentially by degrading SP and inducing NK1R recycling to the plasma membrane (Roosterman et al, 2007;Pelayo et al, 2011). In addition to the role of ECE1 as a regulator of the endocytic signaling of SP-NK1R, ECE1 is a known key enzyme that mediates melanogenesis by catalyzing the specific cleavage of inactive Big-EDN1 to produce an active EDN1 in keratinocytes and endothelial cells (Yanagisawa et al, 1988;Kido et al, 1997), as demonstrated by the increased level of secreted EDN1 in several hyperpigmented lesions (Manaka et al, 2001). ECE1 regulates the endocytic signaling and trafficking of SP1-NK1R and activates EDN1 via direct cleavage; therefore, we initially hypothesized that SP-NK1R-dependent endocytosed ECE1 interacts with and cleaves the inactive Big-EDN1 residing within vesicles in the secretory pathway in human melanocytes.…”
Section: Discussionmentioning
confidence: 96%
“…It is commonly that UV-induced hyperpigmentation is composed of three major steps: the first step is the proliferation of melanocytes (5), followed by increased melanogenesis, and ultimately, the transfer of melanosomes from melanocytes to keratinocytes (6,7). In recent years, the relationships between endothelins and pigment diseases have drawn considerable attention due to the indispensable role of endothelins in epidermal pigmentation in several hyperpigmentary disorders (8,9). As intrinsic mediators for human melanocytes, endothelins play vital roles in UVB-induced pigmentation (8).…”
Section: Introductionmentioning
confidence: 99%
“…ET-1 was firstly isolated from vascular endothelial cells (10), and can induce mitogenesis and melanogenesis in primary human melanocytes (11). The increased secretion of ET-1 is intrinsically considered to be involved in the hyperpigmentation mechanism of SK (9,12). However, the precise mechanisms involved in this process are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperpigmentation may be due to expression of endothelin‐1, a peptide that triggers melanocyte activation . This is the same peptide that has been implicated to partake in the pigmentation process of seborrheic keratosis, actinic keratosis, and basal cell carcinoma …”
Section: Introductionmentioning
confidence: 99%